The Political Economy of the State and Human Rights Violations: A Case Study of the Nigerian State Under the Goodluck Jonathan Administration (2010 – 2015) - Olulana Olubankole Daniel (European Scientific Journal, ESJ, 2017)
In spite of the significant efforts and influence elicited by relevant actors and mechanisms poised playing a watchdog and/or regulatory role over the states activities for an enforcement of human rights protection, the state has been observably seen to continue to record human rights violations across various countries of the world. The case is particularly more sordid for countries of the global South integrated into an international political economy structure that engenders continue far reaching relations of exploitive dominance by states of the global North and their corresponding Dominant Class. This paper examines the outlook of the state’s record of human rights violations under the Goodluck Jonathan Administration to understand if this pattern still holds sway. It also seeks to explain, with the aid of an eclectic theoretical framework constituting a mix of the Marxist and Neo-Liberal theory within the Political economy Approach, whether or not the state may continue to record human rights violations given its nature and character. The study discovered the foregoing statement to be in the affirmative and underscored the relevance of such an understanding in informing the need for the continuing enforcement efforts and influence exerted by the relevant actors and mechanisms for the protection of human rights by states. The study also recommends the need for the adjustment of the international political economy structural outlook to one that is void of an exploitative dominance of the states of the global North as well as the need for Welfarist and other relevant policies central to securing the human rights of the citizenry at a reasonable minimum to be formulated in Nigeria. The role and vibrant activities of the relevant actors and mechanisms is underscored as one central to birthing this reality as was seen in the way they galvanized public popular action in the elections that saw the voting out of the incumbent Ruling Class and its long-standing power holding party in order to birth for the desired leadership of the state that will birth forth the desired reality.